First principles modeling and simulation of Zr-Si-B-C-N ceramics: Developing hard and oxidation resistant coatings. (15th February 2017) - Dasmahapatra, Atreyi; Meletis, Efstathios; Kroll, Peter
Abstract: We model amorphous ZrSiBCN ceramics combining ab-initio molecular dynamic simulations with melt-quench and simulated annealing techniques. Starting from the parent composition Zr42 B32 C8 N18 we systematically increase the Si3 N4 content along four different pathways in the composition diagram and evaluate trends in structure and properties. Mixtures of ZrB2, ZrN, and ZrC exhibit Zr layers as well as ZrB2 and ZrN(C) nuclei, but addition of Si3 N4 reduces structural order in the models. Elastic moduli decrease with increasing Si3 N4 content to values less than expected of a simple mixture model. Thus, while addition of Si3 N4 to amorphous ZrBCN coatings may improve oxidation resistance, this needs to be balanced with desired mechanical properties. Graphical abstract: Image 1